Congenital heart disease is growing up - Thorne, Sara (SA Heart Journal, 2017)
Congenital heart disease is growing up: adult survivors, reaping the benefits of early surgical and percutaneous intervention, outnumber children in many developed countries. Many have little in the way of residual defects and can look forward to a long and healthy life. However, many others reach adulthood with increasingly complex surgically-modified disease – their truly long term outlook is unknown, but patients with complex anatomy and physiology will require careful and creative management, as described in the articles in this edition.